Paenibacillus lemnae sp. nov., an endophytic bacterium of duckweed (Lemna aequinoctialis) - Chokchai Kittiwongwattana; Chitti Thawai (My University, 2014)
A Gram-stain-variable, rod-shaped and endospore-forming bacterium, designated strain L7-75, was isolated from duckweed (Lemna aequinoctialis). Cells were motile with a monopolar flagellum. Phylogenetic analysis of the 16S rRNA gene sequence indicated that strain L7-75(T) belonged to the genus Paenibacillus, and the closest phylogenetically related species were Paenibacillus uliginis N3/975(T) (98.5% 16S rRNA gene sequence similarity), Paenibacillus purispatii ES_M17(T) (98.5%), Paenibacillus lactis MB 1871(T) (98.2%), Paenibacillus campinasensis 324(T) (97.7%), Paenibacillus glucanolyticus S93(T) (97.7%) and Paenibacillus lautus ATCC 43898(T) (97.4%). Growth of strain L7-75(T) was observed at pH 7-10 and at 20-40 °C, and NaCl concentrations up to 5% (w/v) were tolerated. Major cellular fatty acids included anteiso-C15 : 0, C16 : 0 and anteiso-C17:0 that were present at 36.0%, 14.2 % and 10.0% of the total cellular fatty acid profile, respectively. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and phosphatidyl-N-methylethanolamine. MK-7 was the predominant menaquinone. The diamino acid found in the cell-wall peptidoglycan was meso-diaminopimelic acid. The DNA G+C content was 49.1 mol% (Tm). DNA-DNA relatedness values between strain L7-75(T) and its closest relatives ranged from 4.4 to 47.8%. These results indicate that strain L7-75(T) represents a novel species of the genus Paenibacillus, for which the name Paenibacillus lemnae sp. nov. is proposed. The type strain is L7-75(T) ( = BCC 67838(T) = NBRC 109972(T)).
Keywords: Paenibacillus; Diamino acid; Strain (injury); Diaminopimelic acid; Genomics and Phylogenetic Studies